2015
DOI: 10.1007/s00268-015-3264-5
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Voice Outcomes After Robotic Thyroidectomy

Abstract: Up to 2 years post-operatively, robotic thyroidectomy has advantages in terms of recovery of voice symptoms and acoustic parameters over conventional thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 57 publications
2
22
0
2
Order By: Relevance
“…In addition, with regard to the postoperative cosmetic satisfaction and functional outcomes, we previously reported that swallowing function, neck discomfort and paresthesia, and overall quality of life (QOL) after robotic thyroidectomy were similar to those after conventional cervical thyroidectomy and that postoperative cosmesis and voice outcomes were better in the robotic group [15][16][17][18][19][20]. Also, we and other authors demonstrated that the surgical completeness of robotic total thyroidectomy by transaxillary approach was comparable to that of conventional thyroidectomy if the procedure was performed in properly selected patients by expert robotic thyroid surgeons [21][22][23].…”
mentioning
confidence: 96%
“…In addition, with regard to the postoperative cosmetic satisfaction and functional outcomes, we previously reported that swallowing function, neck discomfort and paresthesia, and overall quality of life (QOL) after robotic thyroidectomy were similar to those after conventional cervical thyroidectomy and that postoperative cosmesis and voice outcomes were better in the robotic group [15][16][17][18][19][20]. Also, we and other authors demonstrated that the surgical completeness of robotic total thyroidectomy by transaxillary approach was comparable to that of conventional thyroidectomy if the procedure was performed in properly selected patients by expert robotic thyroid surgeons [21][22][23].…”
mentioning
confidence: 96%
“…However, due to a low threshold of BMI in that study, the mean BMI was 22.0 ± 1.2 Kg/m 2 , even lower than the mean BMI of the 240 patients in our study, which was 23.8 ± 3.9 Kg/m 2 . Nonetheless, most studies from North America report higher BMIs for patients who receive transaxillary robotic thyroidectomy (mean approximately 25.0‐28.7 Kg/m 2 ) than for those in South Korea (mean approximately 22.6‐23.7 Kg/m 2 ) …”
Section: Discussionmentioning
confidence: 99%
“…Robot-assisted transaxillary approach was found to yield better patient outcomes, including reduced pain and increased cosmetic satisfaction (11)(12)(13)(14)(15), postoperative voice change (16), and swallowing discomfort (11,17).…”
Section: Benefits and Drawbacksmentioning
confidence: 99%